Let us draw the figure to understand it
Since m
Since m
Since m
Since m
Then add (9x + 11) and (7x - 5) and equate the sum by 102
![(9x+11)+(7x-5)=102](https://img.qammunity.org/2023/formulas/mathematics/college/rb9czq0d4qryhduh64ax7nxpyhaz35tcub.png)
Add the like terms on the left side
![\begin{gathered} (9x+7x)+(11-5)=102 \\ 16x+6=102 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6uhnsmv76uzu4lrjstwnzjhe380fwg7o8r.png)
Subtract 6 from both sides
![\begin{gathered} 16x+6-6=102-6 \\ 16x=96 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l1j5ybj0ym90zconli74dqljhdv8czoyyr.png)
Divide both sides by 16
![\begin{gathered} (16x)/(16)=(96)/(16) \\ x=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hs9hzi91c1yzmldbmyvfxbtcslj11djtec.png)
Now to find the measure of angle RBP substitute x by 6 in its measure
![\begin{gathered} m\angle RBP=9(6)+11 \\ m\angle RBP=54+11 \\ m\angle RBP=\mathring{65} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sq5gnvwrd30un88ia4pg02wwlsnzqyvdrt.png)